Political dimensions in four Indonesian women’s travel writings: Cultural resistance and ambivalent agency - Jaya, Akmal; Faruk, Faruk; Sudibyo, Sudibyo (Universitas Mulawarman, 2026)
This study examines four Indonesian women’s travel narratives published between 2011 and 2014: The Naked Traveler One Year Round The World Trip (Trinity), The Jilbab Traveler (Asma Nadia), Perempuan Merah Putih (Nungky Irma Nurmala Pratikno), and London: Angel (Windry Ramadhina) through the concept of ambivalent agency by Ullah (2025) and Spivak’s (1994) notion of the double bind. This study reinterprets these contradictions not as conscious political strategies, but as symptoms of a complex, often complicit, negotiation with hegemonic power. The analysis reveals that agency in these texts is achieved through patterned accommodations to the very structures they critique: Trinity articulates agency through self-orientalizing mimicry that internalizes the tourist gaze; Nadia navigates the commodification of piety, transforming the jilbab into a neoliberal lifestyle brand; Nungky operates within the gendered constraints of State Ibuism, performing empowerment only within state-sanctioned nationalism; and Ramadhina utilizes intimate relationality to manage the anxiety of the unhomely. The study concludes that Indonesian women’s travel writing is less a site of pure resistance than a space of ambivalence, where the postcolonial subject must inhabit conflicting norms, simultaneously resisting and reproducing patriarchal and capitalist logics to achieve mobility.